Silicone rubber composite material for enhancing wear resistance of tire and preparation method of silicone rubber composite material

By introducing silicon carbide/alumina heterojunction nanofibers and fluorinated graphene networks into the tire silicone rubber composite, combined with modification treatment and gradient distribution technology, the wear resistance and friction coefficient improvement of tire silicone rubber composite materials is solved, achieving efficient wear resistance and safety improvement.

CN120383825APending Publication Date: 2025-07-29SHANDONG YOUYOU RUBBER TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510409629.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-02
Publication Date
2025-07-29

AI Technical Summary

Technical Problem

When the existing tire silicone rubber composite materials improve wear resistance, a single filler system leads to limited reinforcement effect, and it is difficult to take into account the contradictory demands of reduced friction coefficient and improved surface hardness, and there are problems of poor interface compatibility and crack propagation.

Method used

Silicon carbide/alumina heterojunction nanofibers are used to form a multi-scale enhanced network with fluorinated graphene, and the filler-matrix binding force is enhanced by combining thiol-modified titanium dioxide quantum dots and zinc borate nanosheets. The filler dispersion uniformity is improved through vinyl triethoxysilane modification and ultrasonic dispersion processes, and the step-type mixing strategy and the second-stage vulcanization process are used to optimize the tribological properties and structural stability.

Benefits of technology

Significantly reduces wear consumption by more than 50%, reduces dynamic heat generation by 30%, improves tire service life and enhances driving safety, and is suitable for high-speed heavy-duty tire tread glue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120383825A_ABST
    Figure CN120383825A_ABST
Patent Text Reader

Abstract

The invention discloses a silicone rubber composite material for enhancing the wear resistance of a tire and a preparation method of the silicone rubber composite material, and belongs to the technical field of silicone rubber materials for tires. The silicon carbide nanofibers directionally bear stress through a one-dimensional structure, the surface friction coefficient is reduced through the layered lubricating characteristic of fluorinated graphene, and crack propagation is inhibited on the micro-level through the synergistic effect of the silicon carbide nanofibers and the fluorinated graphene. The tribological performance is further optimized through compound addition of the polyimide microspheres and the nano-diamond powder, dynamic friction loss is reduced through the ball effect, and the surface scratch resistance is improved through the ultra-high hardness of the nano-diamond powder. Meanwhile, the filler-matrix binding force is enhanced through interface bonding of the sulfydryl modified titanium dioxide quantum dots and the zinc borate nanosheets, abrasive particle falling caused by interface stripping is effectively avoided, and the structural integrity of the material is kept under the long-term dynamic load.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of tire silicone rubber materials, and specifically relates to a silicone rubber composite material for enhancing the wear resistance of tires and a preparation method thereof. Background Art

[0002] Tire silicone rubber composite material is a special rubber material obtained by compounding silicone rubber with reinforcing fillers, crosslinking agents and other additives, and has excellent high temperature resistance, low temperature resistance, ozone resistance and chemical resistance. In tire manufacturing, silicone rubber composite materials are mainly used for the sidewalls and treads of tires, which can improve the grip of tires, reduce rolling resistance, and enhance the wear resistance and tear resistance of tires. In addition, the addition of silicone rubber composite materials can also effectively improve the heat dissipation performance of tires, reduce heat accumulation, and extend the service life of tires. The application of this material not only improves the comprehensive performance of tires, but also promotes the development of the tire industry towards a more efficient and environmentally friendly direction.

[0003] However, when improving the wear resistance of silicone rubber in the prior art, the reinforcing effect is often limited due to a single filler system. For example, traditional nano-silica is prone to agglomeration due to poor interfacial compatibility, leading to stress concentration and crack propagation; at the same time, there is a lack of a multi-dimensional synergistic mechanism, and it is difficult to balance the contradictory requirements of reducing the friction coefficient and increasing the surface hardness. Summary of the Invention

[0004] The purpose of the present invention is to provide a silicone rubber composite material for enhancing the wear resistance of tires and a preparation method thereof in order to solve the above-mentioned problems.

[0005] The technical solution adopted by the present invention is as follows: A silicone rubber composite material for enhancing the wear resistance of tires and a preparation method thereof, the composite material comprising: 100 parts by weight of methyl vinyl silicone rubber, 25 - 35 parts by weight of precipitated nano-silica, 8 - 15 parts by weight of silicon carbide / aluminum oxide heterojunction nanofibers, 6 - 10 parts by weight of fluorinated graphene, 5 - 8 parts by weight of polyimide microspheres, 2 - 4 parts by weight of mercapto-modified titanium dioxide quantum dots, 1.2 - 1.8 parts by weight of bis(tetrabutylammonium) disulfide, 1.5 - 3 parts by weight of vinyltriethoxysilane, 1 - 3 parts by weight of zinc borate nanosheets, and 0.5 - 1.5 parts by weight of nano-diamond powder.

[0006] In a preferred embodiment, a preparation method of a silicone rubber composite material for enhancing the wear resistance of tires comprises the following steps:

[0007] S1: Place the methyl vinyl silicone rubber in an open mill and plasticize it at 40 - 50 °C until the rubber compound is uniformly softened to form a matrix premix rubber.

[0008] S2: Mix the precipitated nano-silica with vinyltriethoxysilane and conduct surface modification by high-speed stirring at 80 - 100 °C for 30 minutes to obtain modified nano-silica;

[0009] S3: Add silicon carbide / aluminum oxide heterojunction nanofibers and fluorinated graphene into an ethanol solvent, ultrasonically disperse for 1 hour and then dry to form composite nano-fillers;

[0010] S4: Add the matrix premixed rubber into a mixer, sequentially add the modified nano-silica and the composite nano-fillers, and knead at 60 - 80 °C for 15 minutes until the fillers are uniformly dispersed;

[0011] S5: Add polyimide microspheres, mercapto-modified titanium dioxide quantum dots, zinc borate nanosheets and nano-diamond powder into the mixer in stages, heat up to 90 - 100 °C and knead for 20 minutes;

[0012] S6: After cooling to below 50 °C, add a bis(tetraethylthiuram) disulfide curing agent and continue to knead for 5 minutes until the curing system is completely fused;

[0013] S7: Transfer the kneaded rubber to a flat vulcanizer and preform it into a sheet under a pressure of 10 - 15 MPa;

[0014] S8: First-stage vulcanization: Vulcanize at 160 - 170 °C for 12 - 15 minutes to form a preliminary cross-linked network;

[0015] S9: Second-stage vulcanization: Place the vulcanized rubber in an oven at 200 °C and keep it warm for 4 hours to eliminate residual stress and stabilize the material properties, and then collect the material to complete the preparation process of the silicone rubber composite material with strong tire wear resistance.

[0016] In a preferred embodiment, in step S1, the raw methyl vinyl silicone rubber is put into a two-roll mill, the roller temperature is controlled between 45 °C and 50 °C, the roller gap is adjusted to 1.0 mm to 1.5 mm, and plasticization is carried out at a rotational speed of 15 to 20 revolutions per minute; continuously knead for 8 to 10 minutes, control the thickness of the rubber material between 0.5 mm and 1.0 mm through multiple thin-pass processes to eliminate the initial structural defects of the rubber material until the surface of the rubber material is smooth and has no granular feeling, and the plasticity reaches between 0.35 and 0.45 as measured by a Williams plasticity meter to form a uniform matrix premixed rubber.

[0017] In a preferred embodiment, in step S2, precipitated nano-silica and vinyltriethoxysilane are added to a high-speed mixer, the rotational speed of the stirring paddle is set to 1000 to 1200 revolutions per minute, and it is heated to about 85 °C for dynamic modification treatment; continuous stirring is carried out for 40 minutes, and deionized water accounting for 0.5% of the total amount of the filler is injected three times through a spraying device to promote the hydrolysis and condensation of the silane; after the modification is completed, the mixed material is transferred to a vacuum drying oven and dried at 90 °C for 2 hours, and then a 200-mesh sieve is used to remove hard agglomerates.

[0018] In a preferred embodiment, in step S3, silicon carbide and alumina heterojunction nanofibers and fluorinated graphene are added to an ethanol solvent at a mass ratio of 1:1.2, the solid-liquid ratio is controlled to be 1:20, and an ultrasonic cell disruptor is used to disperse for 50 minutes at a power of 600 watts and a frequency of 20 kHz; after the dispersion is completed, the undispersed particles are separated by a centrifuge at a rotational speed of 8000 revolutions per minute, and the dispersion liquid is placed in an 80 °C oven and dried for 6 hours, and after grinding, a composite nano-filler with a particle size distribution between 50 nm and 200 nm is obtained.

[0019] In a preferred embodiment, in step S4, the matrix premixed rubber is added to the internal mixer cavity, the rotor speed is set to 60 revolutions per minute, and the initial temperature is controlled at about 65 °C; the modified nano-silica and the composite nano-filler are added in three batches, with an interval of 3 minutes between each batch, and the mixing pressure is gradually increased to 0.8 to 1.0 MPa; the total mixing time is 18 minutes, and an on-line torque monitoring system is used to ensure the uniform dispersion of the filler, and the torque fluctuation range does not exceed plus or minus 5%.

[0020] In a preferred embodiment, in step S5, under the condition that the internal mixer is heated to 95 °C, polyimide microspheres with a particle size of 10 to 30 microns, an aqueous solution of mercapto-modified titanium dioxide quantum dots with a concentration of 2% are sprayed, zinc borate nanosheets with an aspect ratio greater than 50, and nano-diamond powder with a particle size of 50 to 100 nm are added in sequence; a stepped mixing strategy is adopted: first, low-speed mixing is carried out at 40 revolutions per minute for 5 minutes, then it is increased to 80 revolutions per minute for high-speed shearing for 8 minutes, and finally, medium-speed mixing is maintained at 70 revolutions per minute for 7 minutes, and nitrogen is introduced throughout the process to prevent oxidation.

[0021] In a preferred embodiment, in step S6, the cooling water circulation system of the internal mixer is turned on to lower the temperature of the rubber material below 45 °C, and the bis(2,4-dichlorobenzoyl) peroxide vulcanizing agent powder is evenly sprinkled; a two-way rotor is used to mix at a rotational speed of 30 revolutions per minute for 6 minutes, and the dead corners of the cavity are cleaned once every 2 minutes through a side wall scraper; the criterion for determining the end of mixing is that there are no visible vulcanizing agent particles on the surface of the rubber material, and the Mooney viscosity is stable between 55 and 58 at 125 °C.

[0022] In a preferred embodiment, in step S7, the kneaded rubber is cut into blocks of 5 kg and placed in the lower die cavity of a flat vulcanizing machine preheated to 70 °C. The two-stage pressing method is adopted: first, pre-press at 5 MPa for 30 s to remove air bubbles, and then increase the pressure to 12 MPa and hold the pressure for 90 s for molding to obtain an unvulcanized sheet with a thickness of 2.0 mm to 2.1 mm and a size of 300 mm by 300 mm.

[0023] In a preferred embodiment, in step S8, the unvulcanized sheet is loaded into a flat vulcanizing mold with an exhaust groove. The vulcanization temperature is set at 165 °C, a pressure of 15 MPa is applied and the automatic exhaust function is turned on. Exhaust for 3 s every 2 minutes, and exhaust a total of 5 times. The vulcanization time is precisely controlled at 13 minutes, and the crosslinking density is monitored in real time by a vulcanization instrument to reach 85% to 90%. After vulcanization is completed, quickly demold and place it on a constant temperature table at 25 °C for cooling and shaping.

[0024] In step S9, the first-stage vulcanized rubber parts are vertically suspended in a forced convection oven, and the temperature is programmed to rise to 200 °C at a rate of 2 °C per minute and kept at a constant temperature for 4 hours. During this period, the box ventilation valve is opened every 30 minutes to remove volatile components. After the material is cooled to room temperature, the flash is removed by sanding to obtain a final product with a surface roughness not exceeding 1.6 μm. The finished product needs to be cured in an environment of about 23 °C and 50% humidity for 24 hours before performance testing.

[0025] In summary, due to the adoption of the above technical solutions, the beneficial effects of the present invention are as follows:

[0026] 1. In the present invention, the silicon carbide / aluminum oxide heterojunction nanofibers introduced into the formula form a multi-scale reinforcement network with fluorinated graphene. The silicon carbide nanofibers bear stress directionally through a one-dimensional structure, and the layered lubrication characteristics of fluorinated graphene reduce the surface friction coefficient. The two work together to inhibit crack propagation at the micro level. The composite addition of polyimide microspheres and nanodiamond powder further optimizes the tribological properties. The former reduces dynamic friction loss through the ball bearing effect, and the latter improves the surface scratch resistance by utilizing ultra-high hardness. At the same time, mercapto-modified titanium dioxide quantum dots and zinc borate nanosheets enhance the filler-matrix binding force through interfacial bonding, effectively avoiding the abrasive particle shedding caused by interfacial peeling, and keeping the material structurally intact under long-term dynamic loads.

[0027] 2. In the present invention, through the pretreatment of nano-silica with vinyltriethoxysilane and the ultrasonic dispersion process, the dispersion uniformity of the filler is significantly improved, and the stress concentration defects caused by agglomeration are avoided. The stepped mixing strategy combined with the nitrogen protection environment ensures the stability of heat-sensitive nano-components during high-temperature processing, and at the same time realizes the gradient distribution of polyimide microspheres and nano-fillers. The two-stage vulcanization process eliminates internal stress while establishing a high-density cross-linked network by precisely controlling the temperature and programmed heating, making the material have both high resilience and dimensional stability. The finally obtained composite material, while maintaining the inherent high-temperature resistance characteristics of silicone rubber, reduces the abrasion loss by more than 50% and reduces the dynamic heat generation by 30%. It is applicable to the field of tread rubber for high-speed heavy-duty tires, and can significantly extend the service life of tires and improve driving safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of the process principle of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0029] In order to make the objectives, technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0030] Example 1:

[0031] Referring to Figure 1 , a silicone rubber composite material for enhancing the wear resistance of tires and its preparation method, the composite material includes: 100 parts by weight of methyl vinyl silicone rubber, 25 parts by weight of precipitated nano-silica, 8 parts by weight of silicon carbide / aluminum oxide heterojunction nanofibers, 60 parts by weight of fluorinated graphene, 5 parts by weight of polyimide microspheres, 2 parts by weight of mercapto-modified titanium dioxide quantum dots, 1.28 parts by weight of bis(tetrabutylammonium) peroxide, 1.5 parts by weight of vinyltriethoxysilane, 1 part by weight of zinc borate nanosheets, and 0.5 part by weight of nano-diamond powder.

[0032] The preparation method includes the following steps:

[0033] S1: Place the methyl vinyl silicone rubber in an open mill and plasticize it at 40 - 50 °C until the rubber compound is uniformly softened to form a matrix premix rubber;

[0034] S2: Mix the precipitated nano-silica with vinyltriethoxysilane and stir at high speed at 80 - 100 °C for 30 minutes for surface modification to obtain modified nano-silica;

[0035] S3: Add the silicon carbide / aluminum oxide heterojunction nanofibers and fluorinated graphene to an ethanol solvent, ultrasonically disperse for 1 hour and then dry to form a composite nano-filler;

[0036] S4: Add the matrix premixed rubber into the internal mixer, and then add the modified nano-silica and composite nano-fillers in sequence. Mix at 60 - 80 °C for 15 minutes until the fillers are uniformly dispersed;

[0037] S5: Add polyimide microspheres, mercapto-modified titanium dioxide quantum dots, zinc borate nanosheets and nano-diamond powder into the internal mixer in stages. Raise the temperature to 90 - 100 °C and mix for 20 minutes;

[0038] S6: After cooling to below 50 °C, add the bis(tetraethylthiuram) disulfide curing agent and continue to mix for 5 minutes until the curing system is completely fused;

[0039] S7: Transfer the mixed rubber to a flat vulcanizer and preform it into a sheet under a pressure of 10 - 15 MPa;

[0040] S8: First-stage vulcanization: Vulcanize at 160 - 170 °C for 12 - 15 minutes to form a preliminary crosslinked network;

[0041] S9: Second-stage vulcanization: Place the vulcanized rubber in an oven at 200 °C and keep it warm for 4 hours to eliminate residual stress and stabilize the material properties. Then collect the material to complete the preparation process of the silicone rubber composite material with enhanced tire wear resistance.

[0042] In step S1, put the methyl vinyl silicone rubber raw rubber into a two-roll mill. Control the roller temperature between 45 °C and 50 °C, adjust the roller gap to 1.0 mm to 1.5 mm, and carry out plasticization at a rotational speed of 15 to 20 revolutions per minute. Keep mixing and turning over for 8 to 10 minutes, and control the thickness of the rubber material between 0.5 mm and 1.0 mm through multiple thin-pass processes to eliminate the initial structural defects of the rubber material until the surface of the rubber material is smooth and has no particle feeling. The plasticity reaches between 0.35 and 0.45 as measured by a Williams plasticity meter, forming a uniform matrix premixed rubber.

[0043] In step S2, add precipitated nano-silica and vinyltriethoxysilane into a high-speed mixer. Set the rotational speed of the stirring paddle to 1000 to 1200 revolutions per minute, and heat to about 85 °C for dynamic modification treatment. Keep stirring for 40 minutes, and inject deionized water accounting for 0.5% of the total amount of the filler three times through a spraying device to promote the hydrolysis and condensation of the silane. After the modification is completed, transfer the mixed material to a vacuum drying oven and dry it at 90 °C for 2 hours, and then use a 200-mesh sieve to remove hard agglomerates.

[0044] In step S3, silicon carbide, alumina heterojunction nanofibers, and fluorinated graphene are added to an ethanol solvent at a mass ratio of 1:1.2, and the solid-liquid ratio is controlled to be 1:20. An ultrasonic cell disruptor is used to disperse the mixture for 50 minutes at a power of 600 watts and a frequency of 20 kHz. After dispersion, the undispersed particles are separated by a centrifuge at a speed of 8,000 revolutions per minute, and the dispersion is dried in an oven at 80 °C for 6 hours. After grinding, a composite nanofiller with a particle size distribution between 50 nm and 200 nm is obtained.

[0045] In step S4, the matrix premixed rubber is added to the internal mixer chamber. The rotor speed is set at 60 revolutions per minute, and the initial temperature is controlled at about 65 °C. Modified nano-silica and the composite nanofiller are added in three batches, with an interval of 3 minutes between each batch, and the mixing pressure is gradually increased to 0.8 MPa to 1.0 MPa. The total mixing time is 18 minutes. An online torque monitoring system is used to ensure the uniform dispersion of the filler, and the torque fluctuation range does not exceed ±5%.

[0046] In step S5, under the condition that the internal mixer is heated to 95 °C, polyimide microspheres with a particle size of 10 μm to 30 μm, an aqueous solution spray of 2% thiol-modified titanium dioxide quantum dots, zinc borate nanosheets with an aspect ratio greater than 50, and nanodiamond powder with a particle size of 50 nm to 100 nm are added in sequence. A stepped mixing strategy is adopted: first, mix at a low speed of 40 revolutions per minute for 5 minutes, then increase to a high speed of 80 revolutions per minute for high-shear mixing for 8 minutes, and finally maintain a medium speed of 70 revolutions per minute for mixing for 7 minutes. Nitrogen is introduced throughout the process to prevent oxidation.

[0047] In step S6, the cooling water circulation system of the internal mixer is turned on to lower the temperature of the rubber compound below 45 °C, and bis(2,4-dichlorobenzoyl) peroxide powder is evenly sprinkled. A two-way rotor is used to mix at a speed of 30 revolutions per minute for 6 minutes, and the dead corners of the chamber are cleaned by a sidewall scraper every 2 minutes. The criterion for determining the end of mixing is that there are no visible vulcanizing agent particles on the surface of the rubber compound, and the Mooney viscosity is stable between 55 and 58 at 125 °C.

[0048] In step S7, the mixed rubber is cut into 5 kg blocks and placed in the lower die cavity of a flat vulcanizer preheated to 70 °C. A two-stage pressing method is used: first, pre-press at 5 MPa for 30 seconds to remove air bubbles, and then increase the pressure to 12 MPa and hold the pressure for 90 seconds for molding to obtain an unvulcanized sheet with a thickness of 2.0 mm to 2.1 mm and a size of 300 mm × 300 mm. Immediately after molding, it is wrapped with a polyethylene film to prevent surface contamination.

[0049] In step S8, the unvulcanized sheet is loaded into a flat vulcanizing mold with exhaust grooves. The vulcanization temperature is set at 165 °C, a pressure of 15 MPa is applied, and the automatic exhaust function is turned on. Exhausting is carried out for 3 seconds every 2 minutes, and a total of 5 exhausts are performed. The vulcanization time is precisely controlled at 13 minutes, and the crosslinking density is monitored in real time by a vulcameter to reach 85% to 90%. After vulcanization is completed, demolding is carried out quickly and the product is placed on a constant temperature table at 25 °C for cooling and shaping.

[0050] In step S9, a section of vulcanized rubber part is vertically suspended in a forced convection oven, and the temperature is programmed to rise to 200 °C at a rate of 2 °C per minute and kept constant for 4 hours. During this period, the box ventilation valve is opened every 30 minutes to remove volatile components. After the material is cooled to room temperature, the flash is removed by sanding to obtain a final product with a surface roughness not exceeding 1.6 microns. The finished product needs to be cured in an environment of about 23 °C and 50% humidity for 24 hours before performance testing.

[0051] Example 2:

[0052] Referring to Figure 1 , a silicone rubber composite material for enhancing the wear resistance of tires and its preparation method. The composite material includes: 100 parts by weight of methyl vinyl silicone rubber, 35 parts by weight of precipitated nano-silica, 15 parts by weight of silicon carbide / aluminum oxide heterojunction nanofibers, 10 parts by weight of fluorinated graphene, 8 parts by weight of polyimide microspheres, 4 parts by weight of mercapto-modified titanium dioxide quantum dots, 1.8 parts by weight of bis(2,4-dichlorobenzoyl) peroxide, 3 parts by weight of vinyltriethoxysilane, 3 parts by weight of zinc borate nanosheets, and 1.5 parts by weight of nanodiamond powder.

[0053] The preparation method includes the following steps:

[0054] S1: Place the methyl vinyl silicone rubber in an open mill and carry out plasticizing at 40 - 50 °C until the rubber compound is uniformly softened to form a matrix premix rubber.

[0055] S2: Mix the precipitated nano-silica and vinyltriethoxysilane, and carry out high-speed stirring at 80 - 100 °C for 30 minutes for surface modification to obtain modified nano-silica.

[0056] S3: Add the silicon carbide / aluminum oxide heterojunction nanofibers and fluorinated graphene to an ethanol solvent, ultrasonic disperse for 1 hour and then dry to form a composite nano-filler.

[0057] S4: Add the matrix premix rubber to an internal mixer, and sequentially add the modified nano-silica and the composite nano-filler, and carry out mixing at 60 - 80 °C for 15 minutes until the fillers are uniformly dispersed.

[0058] S5: Add polyimide microspheres, mercapto-modified titanium dioxide quantum dots, zinc borate nanosheets and nanodiamond powder into the internal mixer in stages, heat up to 90-100 °C and knead for 20 minutes;

[0059] S6: After cooling down to below 50 °C, add bis(tetrabutylammonium) disulfide and continue to knead for 5 minutes until the vulcanization system is completely fused;

[0060] S7: Transfer the kneaded rubber to a flat vulcanizer and preform it into a sheet under a pressure of 10-15 MPa;

[0061] S8: First-stage vulcanization: Vulcanize at 160-170 °C for 12-15 minutes to form a preliminary crosslinked network;

[0062] S9: Second-stage vulcanization: Place the vulcanized rubber in an oven at 200 °C and keep it warm for 4 hours to eliminate residual stress and stabilize the material properties. After that, collect the material to complete the preparation process of the silicone rubber composite material with enhanced tire wear resistance.

[0063] In step S1, put the methyl vinyl silicone rubber raw rubber into a two-roll open mill. Control the roller temperature between 45 °C and 50 °C, adjust the roller gap to 1.0 mm to 1.5 mm, and carry out plasticization at a rotational speed of 15 to 20 revolutions per minute. Keep kneading for 8 to 10 minutes, control the thickness of the rubber compound between 0.5 mm and 1.0 mm through multiple thin-pass processes to eliminate the initial structural defects of the rubber compound until the surface of the rubber compound is smooth and has no particle feeling. The plasticity reaches between 0.35 and 0.45 as measured by a Williams plasticity meter, forming a uniform matrix premixed rubber.

[0064] In step S2, add precipitated nano-silica and vinyltriethoxysilane into a high-speed mixer. Set the rotational speed of the stirring paddle to 1000 to 1200 revolutions per minute, and heat to about 85 °C for dynamic modification treatment. Keep stirring for 40 minutes, and inject deionized water accounting for 0.5% of the total amount of the filler in three times through a spray device to promote the hydrolysis and condensation of silane. After the modification is completed, transfer the mixed material to a vacuum drying oven, dry it at 90 °C for 2 hours, and then use a 200-mesh sieve to remove hard agglomerates.

[0065] In step S3, add silicon carbide and alumina heterojunction nanofibers and fluorinated graphene into an ethanol solvent according to a mass ratio of 1:1.2, control the solid-liquid ratio to 1:20, and disperse for 50 minutes at a power of 600 W and a frequency of 20 kHz using an ultrasonic cell disruptor. After the dispersion is completed, separate the undispersed particles by a centrifuge at a rotational speed of 8000 revolutions per minute, place the dispersion in an oven at 80 °C and dry for 6 hours, and obtain a composite nano-filler with a particle size distribution between 50 nm and 200 nm after grinding.

[0066] In step S4, the matrix premixed rubber is added into the kneading chamber of the internal mixer, the rotor speed is set at 60 revolutions per minute, and the initial temperature is controlled at about 65 °C. The modified nano-silica and composite nano-fillers are added in three batches with an interval of 3 minutes between each batch, and the kneading pressure is gradually increased to 0.8 MPa to 1.0 MPa. The total kneading time is 18 minutes. The online torque monitoring system is used to ensure the uniform dispersion of the fillers, and the torque fluctuation range does not exceed plus or minus 5%.

[0067] In step S5, under the condition that the internal mixer is heated to 95 °C, polyimide microspheres with a particle size of 10 μm to 30 μm, an aqueous solution spray of mercapto-modified titanium dioxide quantum dots with a concentration of 2%, zinc borate nanosheets with an aspect ratio greater than 50, and nano-diamond powder with a particle size of 50 nm to 100 nm are added in sequence. A stepped kneading strategy is adopted: first, mix at a low speed of 40 revolutions per minute for 5 minutes, then increase to a high-speed shear of 80 revolutions per minute for 8 minutes, and finally maintain a medium-speed kneading of 70 revolutions per minute for 7 minutes. Nitrogen is introduced throughout the process to prevent oxidation.

[0068] In step S6, the cooling water circulation system of the internal mixer is turned on to lower the temperature of the rubber compound below 45 °C, and the bis-(2,4-dichlorobenzoyl) peroxide curing agent powder is evenly sprinkled. A two-way rotor is used to knead at a speed of 30 revolutions per minute for 6 minutes, and the dead corners of the cavity are cleaned by the side wall scraper every 2 minutes. The criterion for judging the end of kneading is that there are no visible curing agent particles on the surface of the rubber compound, and the Mooney viscosity is stable between 55 and 58 at 125 °C.

[0069] In step S7, the kneaded rubber is cut into 5-kg blocks and placed in the lower die cavity of a flat vulcanizing machine preheated to 70 °C. A two-stage pressing method is adopted: first, pre-press at 5 MPa for 30 seconds to remove air bubbles, and then increase the pressure to 12 MPa and hold the pressure for 90 seconds for molding to obtain an uncured sheet with a thickness of 2.0 mm to 2.1 mm and a size of 300 mm × 300 mm. After molding, it is immediately wrapped with a polyethylene film to prevent surface contamination.

[0070] In step S8, the uncured sheet is loaded into a flat vulcanizing mold with exhaust grooves. The vulcanization temperature is set at 165 °C, a pressure of 15 MPa is applied, and the automatic exhaust function is turned on. Exhaust for 3 seconds every 2 minutes, and a total of 5 exhausts are carried out. The vulcanization time is precisely controlled at 13 minutes, and the crosslinking density is monitored in real time by a vulcanization instrument to reach 85% to 90%. After vulcanization, it is quickly demolded and placed on a constant temperature table at 25 °C for cooling and shaping.

[0071] In step S9, a section of vulcanized rubber part is vertically suspended in a forced convection oven, and the temperature is programmed to rise to 200 °C at a rate of 2 °C per minute and kept constant for 4 hours. During this period, the box ventilation valve is opened every 30 minutes to remove volatile components. After the material is cooled to room temperature, the flash is removed by sanding to obtain a final product with a surface roughness not exceeding 1.6 microns. The finished product needs to be cured for 24 hours in an environment of about 23 °C and 50% humidity before performance testing.

[0072] It can be seen from the above that:

[0073] In the present invention, the silicon carbide / aluminum oxide heterojunction nanofibers introduced in the formula form a multi-scale reinforcement network with fluorinated graphene. The silicon carbide nanofibers bear stress directionally through a one-dimensional structure, and the layered lubrication characteristics of fluorinated graphene reduce the surface friction coefficient. The two act synergistically to inhibit crack propagation at the micro level. The composite addition of polyimide microspheres and nano-diamond powder further optimizes the tribological properties. The former reduces dynamic friction loss through the ball bearing effect, and the latter improves the surface scratch resistance using ultra-high hardness. At the same time, the mercapto-modified titanium dioxide quantum dots and zinc borate nanosheets enhance the filler-matrix bonding force through interfacial bonding, effectively avoiding the abrasive particle shedding caused by interfacial peeling, and enabling the material to maintain structural integrity under long-term dynamic loads.

[0074] In the present invention, through the pretreatment of nano-silica with vinyltriethoxysilane and the ultrasonic dispersion process, the dispersion uniformity of the filler is significantly improved, avoiding the stress concentration defects caused by agglomeration. The stepped mixing strategy combined with a nitrogen protection environment ensures the stability of heat-sensitive nano-components during high-temperature processing, and at the same time realizes the gradient distribution of polyimide microspheres and nano-fillers. The two-stage vulcanization process eliminates internal stress while establishing a high-density crosslinked network through precise temperature control and programmed temperature rise, making the material have both high resilience and dimensional stability. The finally obtained composite material, while maintaining the inherent high-temperature resistance characteristics of silicone rubber, has a wear loss reduction of more than 50% and a dynamic heat generation reduction of 30%. It is suitable for the field of high-speed heavy-duty tire tread rubber, and can significantly extend the service life of tires and improve driving safety.

[0075] It should be noted that, in this document, relational terms such as first and second are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the term "comprising" or any other variant thereof is intended to cover non-exclusive inclusion, such that a process, method, article, or device comprising a series of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or device. Without further limitation, an element defined by the statement "comprising an..." does not exclude the presence of additional identical elements in the process, method, article, or device comprising the element.

[0076] The above description enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the broadest scope consistent with the principles and novel features disclosed herein.

Claims

1. A silicone rubber composite material for enhancing the wear resistance of tires and a preparation method thereof, characterized in that: The composite material includes: 100 parts by weight of methyl vinyl silicone rubber, 25 - 35 parts by weight of precipitated nano-silica, 8 - 15 parts by weight of silicon carbide / aluminum oxide heterojunction nanofibers, 6 - 10 parts by weight of fluorinated graphene, 5 - 8 parts by weight of polyimide microspheres, 2 - 4 parts by weight of mercapto-modified titanium dioxide quantum dots, 1.2 - 1.8 parts by weight of bis(tetrabutylammonium) disulfide, 1.5 - 3 parts by weight of vinyltriethoxysilane, 1 - 3 parts by weight of zinc borate nanosheets, and 0.5 - 1.5 parts by weight of nano-diamond powder.

2. The preparation method of a silicone rubber composite material for enhancing the wear resistance of a tire according to claim 1, characterized in that: The preparation method includes the following steps: S1: Place the methyl vinyl silicone rubber in an open mill and plasticize it at 40 - 50 °C until the rubber compound is uniformly softened to form a matrix premix rubber. S2: Mix the precipitated nano-silica with vinyltriethoxysilane and stir at high speed at 80 - 100 °C for 30 minutes for surface modification to obtain modified nano-silica. S3: Add the silicon carbide / aluminum oxide heterojunction nanofibers and fluorinated graphene to an ethanol solvent, ultrasonically disperse for 1 hour and then dry to form a composite nano-filler. S4: Add the matrix premix rubber to an internal mixer, and sequentially add the modified nano-silica and the composite nano-filler, and knead at 60 - 80 °C for 15 minutes until the fillers are uniformly dispersed. S5: Add the polyimide microspheres, mercapto-modified titanium dioxide quantum dots, zinc borate nanosheets and nano-diamond powder to the internal mixer in stages, raise the temperature to 90 - 100 °C and knead for 20 minutes. S6: After cooling to below 50 °C, add bis(tetrabutylammonium) disulfide and continue to knead for 5 minutes until the vulcanization system is completely fused. S7: Transfer the kneaded rubber to a flat vulcanizer and preform it into a sheet under a pressure of 10 - 15 MPa. S8: First-stage vulcanization: Vulcanize at 160 - 170 °C for 12 - 15 minutes to form a preliminary cross-linked network. S9: Second-stage vulcanization: Place the vulcanized rubber in an oven at 200 °C and keep it warm for 4 hours to eliminate residual stress and stabilize the material properties, and then collect the material to complete the preparation process of the silicone rubber composite material with strong tire wear resistance.

3. The preparation method of a silicone rubber composite material for enhancing the wear resistance of a tire according to claim 1, characterized in that: In step S1, the raw methyl vinyl silicone rubber is put into a two-roll open mill, the roller temperature is controlled between 45 °C and 50 °C, the roller gap is adjusted to 1.0 mm to 1.5 mm, and it is plasticized at a speed of 15 to 20 revolutions per minute; continuously knead for 8 to 10 minutes, control the thickness of the rubber compound between 0.5 mm and 1.0 mm through multiple thin-pass processes to eliminate the initial structural defects of the rubber compound until the surface of the rubber compound is smooth and has no particle feeling, and the plasticity reaches between 0.35 and 0.45 as measured by a Williams plasticity meter to form a uniform matrix premix rubber.

4. The preparation method of a silicone rubber composite material for enhancing the wear resistance of a tire according to claim 1, characterized in that: In step S2, precipitated nano-silica and vinyltriethoxysilane are added to a high-speed mixer. The rotation speed of the stirring paddle is set to 1000 to 1200 revolutions per minute, and it is heated to about 85 °C for dynamic modification treatment; continuous stirring is carried out for 40 minutes, and deionized water accounting for 0.5% of the total amount of fillers is injected three times through a spraying device to promote the hydrolysis and condensation of silane; after the modification is completed, the mixed material is transferred to a vacuum drying oven and dried at 90 °C for 2 hours, and then a 200-mesh sieve is used to remove hard agglomerates.

5. The preparation method of a silicone rubber composite material for enhancing the wear resistance of a tire according to claim 1, characterized in that: In step S3, silicon carbide and alumina heterojunction nanofibers and fluorinated graphene are added to an ethanol solvent at a mass ratio of 1:1.2, and the solid-liquid ratio is controlled to be 1:

20. An ultrasonic cell disruptor is used to disperse for 50 minutes at a power of 600 W and a frequency of 20 kHz; After the dispersion is completed, the undispersed particles are separated by a centrifuge at a rotation speed of 8000 revolutions per minute. The dispersion liquid is placed in an oven at 80 °C and dried for 6 hours. After grinding, a composite nano-filler with a particle size distribution between 50 nm and 200 nm is obtained.

6. The preparation method of a silicone rubber composite material for enhancing the wear resistance of a tire according to claim 1, characterized in that: In step S4, the matrix premixed rubber is added to the mixing chamber of an internal mixer. The rotation speed of the rotor is set to 60 revolutions per minute, and the initial temperature is controlled at about 65 °C; the modified nano-silica and the composite nano-filler are added in three batches, with an interval of 3 minutes between each batch, and the mixing pressure is gradually increased to 0.8 to 1.0 MPa; the total mixing time is 18 minutes, and an on-line torque monitoring system is used to ensure the uniform dispersion degree of the filler, and the torque fluctuation range does not exceed plus or minus 5%.

7. The preparation method of a silicone rubber composite material for enhancing the wear resistance of a tire according to claim 1, characterized in that: In step S5, under the condition that the internal mixer is heated to 95 °C, polyimide microspheres with a particle size of 10 to 30 μm, an aqueous solution of mercapto-modified titanium dioxide quantum dots with a concentration of 2% are sprayed, zinc borate nanosheets with an aspect ratio greater than 50, and nano-diamond powder with a particle size of 50 to 100 nm are added in sequence; a stepped mixing strategy is adopted: first, mix at a low speed of 40 revolutions per minute for 5 minutes, then increase to a high speed of 80 revolutions per minute for high-shear for 8 minutes, and finally maintain a medium speed of 70 revolutions per minute for mixing for 7 minutes. Nitrogen is introduced throughout the process to prevent oxidation.

8. The preparation method of a silicone rubber composite material for enhancing the wear resistance of a tire according to claim 1, characterized in that: In step S6, the cooling water circulation system of the internal mixer is turned on to lower the temperature of the rubber compound to below 45 °C, and bis(2,4-dichlorobenzoyl) peroxide powder is evenly sprinkled; a two-way rotor is used to mix at a rotation speed of 30 revolutions per minute for 6 minutes, and the dead corners of the cavity are cleaned by a side wall scraper every 2 minutes; the criterion for judging the end of mixing is that there are no visible vulcanizing agent particles on the surface of the rubber compound, and the Mooney viscosity is stable between 55 and 58 at 125 °C.

9. The preparation method of a silicone rubber composite material for enhancing the wear resistance of a tire according to claim 1, characterized in that: In step S7, the mixed rubber is cut into 5 kg blocks and placed in the lower die cavity of a flat vulcanizing machine preheated to 70 °C; a two-stage pressing method is adopted: first, pre-press at 5 MPa for 30 seconds to remove air bubbles, and then raise to 12 MPa for pressure holding for 90 seconds to form an unvulcanized sheet with a thickness of 2.0 to 2.1 mm and a size of 300 mm by 300 mm.

10. The preparation method of a silicone rubber composite material for enhancing the wear resistance of a tire according to claim 1, wherein: In the step S8, the unvulcanized sheet is loaded into a flat vulcanizing mold with exhaust grooves. The vulcanization temperature is set at 165 °C, a pressure of 15 MPa is applied, and the automatic exhaust function is turned on. Exhausting is carried out for 3 seconds every 2 minutes, with a total of 5 exhausts; the vulcanization time is precisely controlled to be 13 minutes, and the crosslinking density is monitored in real time by a vulcameter to reach 85% to 90%; after vulcanization is completed, demolding is carried out rapidly and the product is placed on a constant temperature table at 25 °C for cooling and shaping; In the step S9, the first-stage vulcanized rubber part is vertically suspended in a forced convection oven, and the temperature is programmed to rise to 200 °C at a rate of 2 °C per minute and kept constant for 4 hours; during this period, the box ventilation valve is opened every 30 minutes to remove volatile components. After the material is cooled to room temperature, the flash is removed by sanding to obtain a final product with a surface roughness not exceeding 1.6 microns; the finished product needs to be aged for 24 hours in an environment of about 23 °C and 50% humidity before performance testing.

Citation Information

Cited By

  • Tire tread material, preparation method thereof and tire

    CN122255743A